Crystal structure of triaqua-(5-bromoisophthalato-κ1 O)-(2,2′-bipyridine-κ2 N:N′)nickel(II) hydrate, C18H19BrN2NiO8 - Shi Zhen-Zhen; Chen Jun-Ling (Zeitschrift für Kristallographie - New Crystal Structures)
C18H19BrN2NiO8, monoclinic, P21/n (no. 14), a = 16.7861(4) Å, b = 7.0732(2) Å, c = 17.1041(4) Å, β = 102.674(2)° $102.674(2){}^{°}$ , V = 1981.31(9) Å3, Z = 4, R gt(F) = 0.0340, wR ref(F 2) = 0.0670, T = 293(2) K.